DESIGN-BASED RESEARCH TO DEVELOP SFL-INFORMED TBLT INSTRUCTIONS: REFLECTION FROM ESP COURSE - Nurhadianty Rahayu; Hikmah Pravitasari (STKIP PGRI Jombang, 2021)
Design-based research (DBR)’s use in education research has been manifold since it provides teacher-researcher collaboration in order to improve theoretical understandings and plan an intervention to a non-optimal learning condition. Plethora of studies utilize the methodology to design and develop macro pedagogic documents, professional development programs, and refine the theoretical understanding in real classroom practices. However, its use for developing a set of instructional designs that promote critical meaning-making and reflection in English for Specific Purposes (ESP) courses is relatively scarce. The iterative cycle of DBR affords us to co-create the instructional design that utilizes some systemic functional linguistic (SFL) concepts to task-based language teaching (TBLT) in supporting students’ critical meaning-making. Students report they find TBLT suitable for their pace of learning as it organizes the pedagogic tasks in a sequential manner. Even though SFL concepts to approach texts were initially seen challenging, but with explicit instruction and scaffolding, they can carry on with the demands of the tasks. This informs that SFL-informed TBLT can be also adapted to a wider variety of contexts, adapting DBR cycles.